Synthesis and structural characterization of a new SbPO4-GeO2 glass system - Montesso, Murilo [UNESP] (2018)
This work presents the production and characterization of a new prolific binary glass system based on SbPO4-GeO2. The dependence of GeO2 content on thermal, structural and optical properties were investigated by means of thermal analysis, Raman, UV–Vis-NIR, infrared, M-lines and EPR spectroscopy. Glass transition temperatures remain constant around 410 °C when GeO2 content is increased, indicating that GeO4 units are not responsible for increasing the connectivity of PO4 units. Thermal stability linearly increases as a function of GeO2 content, reaching a value around 400 °C for glass containing 90 mol% of GeO2. Raman spectroscopy was used to evaluate the glass structural changes when GeO2 is incorporated from 30 to 90 mol% indicating a gradual change from a phosphate to a germanate glass skeleton. The optical window extends from 350 nm at UV region, up to 2.7 μm in the middle-infrared region limited by the multiphonon cut-off due to the strong OH absorption. M-lines technique shows that increasing GeO2 content decreases the refractive index, mainly because the lower concentration of higher polarizable antimony atoms. EPR spectra of heat treated V2O5 doped glasses, at different temperatures above the glass transition temperature, shows the characteristic eight-line hyperfine splitting spectrum. The spin Hamiltonian parameters obtained from the simulated spectra indicates that the paramagnetic tetravalent vanadium ions in the glasses exist as vanadyl form VO2+, located in axially distorted octahedral sites. For glasses treated at higher temperatures a second VO2+ component appears in the EPR spectra and the analysis of the spin-Hamiltonian parameters suggests that these vanadyl ions are in more tetragonal distorted octahedral sites than those in the glass.